Accounting in Management of an Enterprise - Lakis, Vaclovas (Ekonomika, 2001)
Two forms of accounting are used at an enterprise, namely, a financial accounting and a management accounting. The purpose of a financial accounting is a presentation of information on the property and financial position of the enterprise. Financial accounting is regulated by laws, standards, other normative acts. The main product of this accounting is a financial statement. It is most frequently used by external users. Because of different economical, historical and other conditions three main models of accounting were formed: the British-American, the Continent and the South American. However, a globalization of economy and an appearance of international corporations dictated a necessity to harmonize a financial accounting. So, regional and world bookkeeping organizations appeared. International Accounting Stan· dards and Directives of European Union were developed. The requirement of bookkeeping laws and other normative acts of various states are coordinated with these Standards and Directives. The purpose of management accounting is a provision of information necessary for a management of an enterprise. It is not or almost is not regulated, so it is more individualized and adapted to the specified enterprise. Within last decades management accounting professionals developed and introduced many innovations which considerably extended its possibilities. They include a calculation according to ABC conception, an acquisition of raw and other materials according to Just-in-time systems, methodics of an estimation of the activities of the enterprise upon conditions of an inflation. On an application of ABC conception the indirect expenses are calculated OD the base of various criteria, on which these expenses depend. This enables to calculate more exactly the cost price of the product and to determine its structure. The basic principle of the Just-in-time system is a supply of all the component, necessary for the production, just on the moment, when they are necessary. This allows to avoid large stocks and storehouses. An application of management accounting methods allows to calculate more precisely the results of the activities of an enterprise and simultaneously protect property rights of the proprietor. More attention should be paid to an improvement of accounting in Lithuania. A comprehensive law on bookkeeping and national accounting standards are necessary. It would be purposeful to establish a management accounting institute - a professional organization, financed by the state and private enterprises and engaged in a development of management accounting.